If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12x + 4 = -24x + 40 Reorder the terms: 4 + -12x = -24x + 40 Reorder the terms: 4 + -12x = 40 + -24x Solving 4 + -12x = 40 + -24x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '24x' to each side of the equation. 4 + -12x + 24x = 40 + -24x + 24x Combine like terms: -12x + 24x = 12x 4 + 12x = 40 + -24x + 24x Combine like terms: -24x + 24x = 0 4 + 12x = 40 + 0 4 + 12x = 40 Add '-4' to each side of the equation. 4 + -4 + 12x = 40 + -4 Combine like terms: 4 + -4 = 0 0 + 12x = 40 + -4 12x = 40 + -4 Combine like terms: 40 + -4 = 36 12x = 36 Divide each side by '12'. x = 3 Simplifying x = 3
| 10x-116=4x-14 | | x/26=10 | | (100+x)+x=110 | | 6.75+2.25x= | | -x+5=x+4 | | 4+35x=28x+8 | | 2y^2=9-4y | | 12+8q=15+7q | | 2(x+1)-3=3x-4 | | a=(12.5)(14.75) | | 72+2x+x=180 | | 2500+300=5000 | | -9-4x=-53x | | 6x-10=4x+4 | | 9y+3=5y+12 | | 100=(x*0.4)+(x*0.4)*0.4+(x*0.4)*0.4*0.4+(x*0.4)*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4*0.4 | | 100=(x*0.4)+(x*0.4)*0.4+(x*0.4)*0.4*0.4+(x*0.4)*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4*0.4 | | 100=(x*0.4)+(x*0.4)*0.4+(x*0.4)*0.4*0.4+(x*0.4)*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4*0.4 | | 100=(x*0.4)+(x*0.4)*0.4+(x*0.4)*0.4*0.4+(x*0.4)*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4*0.4 | | 13-6x=5-7x | | 15x^2-19x=10 | | b+52=64 | | 6x+6=-54-4x | | 3(g+5)=36 | | (7-4i)(5+8i)= | | 12x+1=2x+3 | | 5g+g=12 | | 5+-2x=3x+1 | | 2(x+11)=0 | | 34=6-5x | | 19=9x+4-6x | | 5y+3(y-8)=5(y+1)-3 |